Reator de Arco Elétrico submerso em meio líquido para Síntese de Nanotubos de Carbono. - Trevisan, Luciano Schons (2009)
This paper explain about the design and construction of an electric arc discharge reactor to synthesis of carbon nanotubes, using graphite rods as precursors. Unlike the conventional method, it uses the water into open vessel to isolate the reaction of external environment, without needing a sealed and pressurized chamber immersed in inert gas. The project is divided into three parts: mechanical, electronics and software. Preliminary tests provided initial values for the electric current applied to the graphite electrodes during the cycles of synthesis. It was performed in order to ensure the operation of electromechanical system. The samples formed in the reactor were characterized by Raman spectroscopy and Thermal Gravimetric Analysis techniques. Different types of nanostructures were observed in colected samples. The results indicated the presence of low percentage of amorphous carbon in the material formed, as well as the presence of multiple wall carbon nanotubes. The apparatus allows the easy manipulation of the parameters involved in synthesis therefore is able to promot the growth of nanostructured materials so selective and controlled.